2006
DOI: 10.17221/3947-cjas
|View full text |Cite
|
Sign up to set email alerts
|

The use of extruded chickpeas in diets for growing-finishing pigs

Abstract: AbstrAct:The effect of partial and total replacement of soybean meal (SBM) with extruded chickpeas (Cicer arietinum L.) and partial replacement of SBM with raw chickpeas on pig growth and carcass characteristics was determined in a 17 week experiment. Sixty growing-finishing pigs were allocated to five dietary treatments: CKP0, ECKP100, ECKP200, ECKP300 and CKP100 of 12 animals each, and received a diet ad libitum. The diet for CKP0 treatment had no chickpeas (control), while those for treatments ECKP100, ECKP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…As observed with other legumes such as FB and FP, CKP contains ANFs such as amylase and protease inhibitors, as well as lectins and polyphenols [ 15 , 86 ]. The use of extrusion and heat treatments on raw CKP has been reported to remove most of the ANF and increase its utilization in the diets of pigs and broiler chickens [ 38 ]. Inclusion of CKP in diets of weaned pigs at 30% reduced growth, feed efficiency, and protein digestibility, but did not impact feed intake and energy digestibility [ 16 ].…”
Section: Protein-rich Feed Ingredientsmentioning
confidence: 99%
See 1 more Smart Citation
“…As observed with other legumes such as FB and FP, CKP contains ANFs such as amylase and protease inhibitors, as well as lectins and polyphenols [ 15 , 86 ]. The use of extrusion and heat treatments on raw CKP has been reported to remove most of the ANF and increase its utilization in the diets of pigs and broiler chickens [ 38 ]. Inclusion of CKP in diets of weaned pigs at 30% reduced growth, feed efficiency, and protein digestibility, but did not impact feed intake and energy digestibility [ 16 ].…”
Section: Protein-rich Feed Ingredientsmentioning
confidence: 99%
“…Paszkiewicz et al [ 69 ] reported a reduction in saturated fatty acids and an increase in the unsaturated fatty acids composition of the subcutaneous fat in broiler chickens when CKP was included in broiler chicken diets. It has been suggested that CKP can be included in diets of weaning pigs at 15% [ 16 ], finishing pigs at 30% [ 15 , 38 ], and broiler chickens at 12–15% [ 39 , 89 ].…”
Section: Protein-rich Feed Ingredientsmentioning
confidence: 99%